PermainanTradisionalAnak-Anak Di Kampung NagaSebagai Ide BerkaryaConceptual Photography - Arian Adi Pratama, - (2018)
Permainantradisionalsudahmulaidilupakanolehanak-anak. Masakanak-kanakmerupakan momentum yang tidakluputdarikegembiraandan proses berkembangdimanaapa yang di dapatkanpadasaatmasihanak-anaksangatberpengaruhuntukmenjadipribadi yang lebihbaik.Kehadiranpermainanelektronikmengungguliminatanak-anakuntukmemainkanpermainan yang membuatanaklebihmemilihpermainan modern daripadapermainantradisional. Hal ini yang menjadirumusanmasalahyaitubagaimanamengembangkansebuahgagasandanmemvisualisasikankaryaseniconceptual photography yang mengangkattemapermainantradisionalanak-anak di Kampung Naga dengantujuanadanyaharapanpengenalanuntukanak-anakusiadiniyang sudahterpengaruhdenganpermainan modern. Penulis memiliki gagasan untuk membuat karyaduadimensidenganjenisconceptual photography memvisualisasikankegiatan yang biasadilakukanolehanak-anak di masalalu. Permainanrakyatadalahsuatu media pembelajaran yang bisamembantudalam proses perkembangananakbaikdarisegikognisianak.Karya yang dibuatdarihasilobservasigunamendapatan data yang benarmengenaipermainantradisionalkemudianmenuangkankedalam ide gagasan. Membuatproperti, mencari model, menentukanlatartempatberkaryalalumengeditgambar, sehinggamenjadikaryasenifotografi yang komunikatifdanmemilikiinovasibarudenganmencetakfoto di media kayuberukuan 75 X 50 cmsebanyaklimakarya.Beberapa proses inimenjaditantanganbagipenulisuntukmengenalkankembalikepadaanak-anaktentangpermainantradisionalmelaluiapresiasikaryaini. ;---Traditional games have begun to be forgotten by children. Childhood is a momentum that does not escape the excitement and the developing process where what is gained when a child is very influential to become a better person. The presence of electronic games outperforms children's interest in playing games that make children prefer modern games rather than traditional games. This is the formulation of the problem, namely how to develop an idea and visualize the conceptual photography artwork that raises the theme of traditional children's games in g Naga Village with the aim of introducing hope for early childhood children who have been influenced by modern games. The author has the idea to create two-dimensional works with the type of conceptual photography to visualize activities that are commonly done by children in the past. Folk game is a learning medium that can help in the process of child development both in terms of child cognition. Works made from observations in order to get the correct data about traditional games then pour into ideas. Make a property, look for a model, determine the setting where to work and edit the image, so that it becomes a communicative art work of photography and has new innovations by printing photos in wood media with 75 X 50 cm in size as many as five works. Some of these processes are a challenge for the author to reintroduce children about traditional games through appreciation of this work.